The Protective Role of Rutin on some Biochemical and histological parameters induced-hyperlipidemia by Triton WR1339 in male rats - Brybr, Khaled O.; Al-Mayali , Hussein Khudair (International Journal of Psychosocial Rehabilitation, 2020)
Rutin (3,3, 4′, 5, 7-pentahydrohyflavone-3-rhamnoglucoside) is a flavonoid of the flavonol type. Rutin is found in many plants and is also an important dietary constituent of food and plant-based beverages. Rutin has several pharmacological properties including antioxidant activities. Also, it was identified that rutin is the major low-density lipoprotein (LDL) antioxidant compound of mulberry in an study. The effects of rutin were tested by using it as induced-hyperlipidemia by Triton WR1339. Male rats were fed 4 weeks with rutin (30mg/kg) to study the hyperlipidemia effects of rutin on serum lipid levels, hepatic enzyme activity, and liver tissue. gavaged the animals with Triton WR1339 resulted in marked hyperlipidemia and increased the serum level of LDL cholesterol (LDL-C). Rutin (at 30 mg/kg) alone significantly reduced the levels of total cholesterol, and LDL-C and also markedly decreased liver enzymes and weight in animals with a high-cholesterol diet. Our findings show that 30 mg/kg of rutin alone or with other supplementation lowered liver weight and enzymes as well as serum total cholesterol and LDL. The hepatic histopathological results reflect the correlation of rutin with liver weight and the levels of serum total cholesterol and LDL-C. These results indicate that rutin has increased anti hyperlipidemia effects in an animal model.